Desenvolvimento de um ELISA in house indireto baseado na proteína p24 recombinante para diagnóstico da leucose enzoótica em bovinos - Andreolla, Ana Paula (2017)
Bovine Leukemia Virus (BLV) is the etiological agent of enzootic bovine leukemia (EBL) a persistent infectious disease highly prevalent in dairy cattle. Serological testing and culling infected animals are central to disease control. The agar gel immunodiffusion (AGID) assay that uses BLV cultivated in Fetal Lamb Kidney cells is the only assay produced in Brazil and used in most laboratories for EBL diagnosis. Aiming to fulfil this gap, we developed an indirect ELISA based on the recombinant capsid protein (p24) of BLV to detect antibodies in cattle. To reach our goals, we designed PCR primers to amplify the nucleotides coding for the p24 protein and cloned the resulting DNA fragment in the pET-20 plasmid. The resulting plasmid was transformed in competent E. coli ER2566 and the protein expression was induced by IPTG (0.1mM). The protein (BLVp24r) was purified using a HisTrap column coupled to an ÄKTA Pure Chromatography equipment, and later analyzed by SDS-PAGE. The antigenicity and immunogenicity of the BLVp24r were evaluated by Western blot using sera from rats immunized with BLVrp24 and with sera from naturally infected cows prior to the development of the ELISA. For the ELISA, the microplate type, antigen concentration and serum dilution were determined by checkboard analysis. The receptor operation characteristics (ROC) curve analysis and the area under the curve (AUC) analysis were used to evaluate the ELISA performance. After that, the ELISA was used to evaluate the prevalence of anti-BLV antibodies in cattle blood. The BLVp24r protein was expressed as a fusion protein and had a molecular mass of 67 KDa. Only the serum from immunized rats and from cattle naturally infected with BLV recognized the BLVp24r by Western blot. The PolySorp® plates provide the bestperformance on the BLVp24r ELISA with 50 ng/well of the protein and with bovine serum diluted 1:100. Our indirect ELISA to BLV was set with a cut-off value of 0.320 at OD450nm and had sensibility of 98.5% and 100% specificity. The ROC had an AUC value of 0.9989 (95% confidence interval from 0.9961 to 1.002), indicating high level of precision. With this ELISA we screened sera samples from cattle and found a prevalence of antibodies to BLV in 31.1% of dairy cattle and 9.5% in beef cattle. The BLVp24r is suitable to detect antibodies to BLV in bovine serum by ELISA and should be a strong candidate for the development of a commercial assay aimingto control EBL in cattle.